2022
DOI: 10.3390/ma15134381
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion–Resistance Mechanism of TC4 Titanium Alloy under Different Stress-Loading Conditions

Abstract: Titanium alloys have now become the first choice of tubing material used in the harsh oil- and gas-exploitation environment, while the interaction of force and medium is a serious threat to the safety and reliability of titanium alloy in service. In this paper, different stresses were applied to TC4 titanium alloy by four-point bending stress fixture, and the corrosion behavior of TC4 titanium alloy was studied by high-temperature and high-pressure simulation experiments and electrochemical techniques, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It was reported that in an oxygen-containing or corrosive ion environment, a continuous and dense passive film can easily and rapidly form on the surface of titanium alloys, which reduces the surface-active dissolution areas and improves corrosion resistance for titanium alloys by hindering the transmission of reactive particles [6][7][8]. But in a marine environment, the huge cyclic load on the titanium alloy can inevitably damage the integrity of the passive film and result in a decrease in its corrosion resistance because chloride ions easily destroy and pass through the passive film on the surface, making contact with the matrix [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in an oxygen-containing or corrosive ion environment, a continuous and dense passive film can easily and rapidly form on the surface of titanium alloys, which reduces the surface-active dissolution areas and improves corrosion resistance for titanium alloys by hindering the transmission of reactive particles [6][7][8]. But in a marine environment, the huge cyclic load on the titanium alloy can inevitably damage the integrity of the passive film and result in a decrease in its corrosion resistance because chloride ions easily destroy and pass through the passive film on the surface, making contact with the matrix [9].…”
Section: Introductionmentioning
confidence: 99%